Shelling, Sniping and Starvation: The Law of Armed Conflict and the Lessons of the Siege of Sarajevo - Riordan, KJ (Victoria University of Wellington Law Review, 2010)
This article looks at the siege of Sarajevo conducted from April 1992 to February 1996, which resulted in the loss of thousands of lives and great suffering to the civilian population of the city. It also resulted in criminal convictions for Bosnian Serb commanders Stanislav Galić and Dragomir Milosević. Given the fact that sieges have been a common form of warfare from antiquity to the present day, and are likely to remain so, these convictions and the heavy sentences that accompanied them must provide a cautionary tale for commanders who may in future be required to undertake such an operation. This article examines the traditional methods of warfare associated with the successful prosecution of a siege and contrasts them with the detailed and onerous provisions of the law of armed conflict. It ponders the question of what a modern commander must do to conduct a siege which is both lawful and successful.